Rescue intracranial stenting for acute ischemic stroke after the failure of mechanical thrombectomy: A systematic review, meta-analysis, and trial sequential analysis - Cai, Junxiu; Xu, Hai; Xiao, Rongzhou; Hu, Liping; Xu, Ping; Guo, Xianbin; Xie, Yu; Pan, Min; Tang, Jie; Gong, Qingtao; Liu, Yan; Su, Rong; et al. (Frontiers in Neurology, 2023)
Background Intracranial rescue stenting (RS) might be an option for acute ischemic stroke after the failure of mechanical thrombectomy (MT). However, the findings were not consistent in previous systematic reviews, and whether the conclusion was supported by sufficient statistical power is unknown. Aim To examine the effect of RS on acute ischemic stroke after the failure of MT with a systematic review, meta-analysis, and trial sequential analysis (TSA). Methods We searched Ovid Medline, Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL) from inception to 15 June 2022, without any language restriction. Studies assessing the effect of RS for acute ischemia stroke after MT failure were included. Two reviewers independently screened the retrieved articles, extracted data, and evaluated the quality of the included studies through the New Ottawa Scale (NOS). The primary outcome was the recanalization rate after RS. Secondary outcomes included modified Rankin Scale (mRS) at 3 months after stroke, symptomatic intracranial hemorrhage (sICH), and mortality rate. We synthesized the data through a random-effects model and performed a TSA analysis. Results We included 15 studies (containing 1,595 participants) after screening 3,934 records. The pooled recanalization rate for rescue stenting was 82% (95% CI 77–87%). Compared with non-stenting, rescue stenting was associated with a higher proportion of patients with 0–2 mRS score (OR 3.96, 95% CI 2.69–5.84, p < 0.001) and a lower 90-day mortality rate (OR 0.46, 95% CI 0.32–0.65, p < 0.001), and stenting did not increase sICH rate (OR 0.63, 95% CI 0.39–1.04, p = 0.075). The TSA analysis showed that the meta-analysis of the mRS score had a sufficient sample size and statistical power. Conclusions Our study showed that rescue stenting was effective and safe for patients with acute ischemia stroke who also had a failed MT, and this result was confirmed in a TSA analysis.